Slon trabalski i inne wiersze - Tuwim, Julian, 1894-1953.; Sedlaczek, Joanna (Warszawa : Nasza Ksiegarnia, 1993)
A collection of humorous verse for elementary and pre-school children. Ages 4-10.
"Lektura klasa 2" -- front cover.
Keywords: Children's poetry, Polish